Openness to experience - a moderator between social commerce success factors and customer satisfaction relationship: facebook brand page platform / Ariff Md. Ab. Malik, Hanitahaiza Hairuddin and Nurfaznim Shuib. - Md. Ab. Malik, Ariff; Hairuddin, Hanitahaiza; Shuib, Nurfaznim (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2018)
Nowadays, the role of social media in marketing strategies is undeniable. Facebook brand page is one of the platforms used by the marketers to promote their products. The purpose of this study is to investigate whether the Openness to Experience personality moderates the relationship between Information System Success (ISS) factors and customer satisfaction using a sample of 354 customers from three different Facebook brand pages. The result found that the Openness to Experience personality effect the relationship between ISS factors and customer satisfaction. Meanwhile, the Information Quality is the most important factor that influences the customer satisfaction towards social media applications.